Conservation value of Beeshhazari Lake: an insight into diversity and abundance of wetland birds (Our Nature, 2018)
Beeshazari and associated lakes play the vital roles in providing feeding and breeding grounds for a large number of wetland fauna including many migratory birds. Wetland dependent birds in Beeshazari lake system was studied by using Area Search and Scan Sampling methods. We recorded a total of 44 wetland bird species belonging to 11 families and 9 orders. These lakes support a total of 7.5% of globally threatened and 8.93% of the nationally threatened birds. The species diversity and abundance were more in winter than in summer seasons. Fishermen and tourist pressure caused significantly negative impact on abundance and distribution of wetland birds. The major threats to wetland birds in this area were human disturbance, habitat degradation and declining water quality due to eutrophication and invasion of alien plant species such as water Hyacinth and Southern Cutgrass. Therefore, such threats need to be addressed for the long-term survival of wetland birds and extension of conservation value of Beeshazari lake system.